Influence of Altered Knee Angle on Electromyographic Activity of Hamstring Muscles Between Nordic Hamstring Exercise and Nordic Hamstring Exercise with Incline Slope Lower Leg Board - Taspol Keerasomboon; Toshiaki Soga; Norikazu Hirose (North American Sports Medicine Institute, 2022)
# Background Previous studies have shown that performing the Nordic hamstring exercise (NHE) with different board slope angles can affect hamstring activation. However, changes in muscle length with different board slopes can alter joint angles leading to the moment arm (MA) at the knee changing during the NHE. # Purpose This study aimed to investigate the influence of changing muscle length on hamstring electromyographic activity during an isometric NHE, while maintaining an equal moment arm. # Study Design A crossover study design # Methods Sixteen male volunteers performed two types of conventional NHE, one with knees on the floor (NHE) and one with the legs placed upon an incline slope of a lower leg board (NHEB). To compare between the conventional and inclined NHE, the moment arm at the knee was calculated to be equal by an examiner holding the lower legs at points marked at 77% and 94% of the length of the lower leg. The four sub-groups comprised of: 1) NHE-77%, 2) NHE-94%, 3) NHEB-77%, and 4) NHEB-94%. The hamstring EMG activity was measured at the biceps femoris long head (BFlh) and at the semitendinosus (ST) and related compensatory muscles. The RMS data were normalized as a percentage of the maximum isometric values (normalized EMG \[nEMG\]). Significant main effects findings were followed up with Tukey's post-hoc test using SPSS software and statistical significance was set at the p \< 0.05 level. # Results The BFlh EMG activity values for NHE-77% were significantly higher than those for NHE-94% (p= 0.036) and NHEB-77% (p \< 0.001), respectively, while ST during NHE-77% was significantly higher only in NHEB-77% (p \< 0.001). In addition, NHEB-94% was significantly greater than NHEB-77% for both BFlh (p \< 0.001) and ST (p \< 0.001). # Conclusion These results indicate that hamstring electromyographic activity is decreased when the hamstring muscle is lengthened during the Nordic hamstring exercise. # Level of Evidence 3